Implementasi Pendekatan Saintifik pada Mata Pelajaran AlQuran Hadis - Afifah Ayun Burhani; A. Sulaeman (Proceedings Series on Social Sciences & Humanities, 2023)
The 2013 curriculum using a scientific was officially implemented simultaneously in 2014 in all schools, including the primary and secondary education environment. Approach scientific islearner-centeredd learning. The learning approach scientific provides opportunities for students to carry out exploration and elaboration of the material to be studied, as well as providing opportunities for students to be able to actualize their abilities or talents through learning activities that have been planned by the teacher. This study aims to determine the implementation of the science in the subjects of Qur'an Hadith at SMP Muhammadiyah 2 Purwokerto starting from the planning, and implementation to the evaluation process. This research is a type of field research (field research). The subjects in this study were Qur'an Hadith teachers and representatives of class VII students. Data were collected using observation, interviews, and documentation methods. The data were analyzed descriptively and qualitatively through data reduction (data reduction), data presentation (data display), and drawing conclusions. The results showed that in the planning process, the teacher made a Learning Implementation Plan (RPP) which referred to the ISMUBA syllabus, the teacher looked for materials through books and the internet, and prepared to learn media. The process of applying or implementing a scientific in learning, namely observing, asking, trying, reasoning, and communicating has been implemented by the teacher completely and coherently. Evaluation of the implementation of learning found that the lack of readiness of students to learn, lack of activeness of students in asking questions, there are some students who have not been able to read the Qur'an so they do not contribute to the discussion process, especially in the subjects of Qur'an Hadith.